Staying afloat : the water smarts for survival campaign - Fernando, Grace Keng (2008)
This dissertation is an exercise in applying the principles and techniques of campaign design. In order to do so, it draws on literature from the field which includes Andreasen, Colle, Rogers, Rice and Atkins, Mendelsohn, and Schultz, Tannenbaum and Lauterbom, among others. Further sources have their origins in organisations and authorities in Singapore, me Internet, The Straits Times and Reuters news service. Also used are a variety of practical methods culled from agencies in Singapore, such as the Ministry of Health and Traffic Police, which produce campaigns here. Other reference points include campaigns conducted in the United States and New Zealand.